Experimental study of low-velocity impact on foam-filled kraft paper honeycomb structure - Abdul Kadir, Nurdina; Aminanda, Yulfian; Shaikh Dawood, Mohd. Sultan Ibrahim; Mokhtar, Hanan (IOP, 2018)
Low-velocity impact tests of unfilled and foam-filled Kraft paper honeycomb are carried out to investigate the effect of foam, indenter size and location of indentation on maximum or peak force and energy absorption capability. In this study, three indenter sizes (10mm, 12mm, 15mm) and three different locations of indentation (vertical edge, double wall and single wall) were used and compared. The test results show that the foam is given a significant increment of peak force and specific energy absorption to the honeycomb structure subjected to indentation load. The peak force and energy absorption capability also effected by indenter size which due to the contact area of indentation. As for the location of indentation, vertical edge gives highest peak force and energy absorption by the fact that vertical edge is the intersection of three walls of honeycomb cell.